2020
DOI: 10.3390/eng1020005
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Empirical Calculation System for Predicting the Seepage Discharge and Free Surface Location of Earth Dam over Horizontal Impervious Foundation

Abstract: In the numerical analysis of the Laplace equation, which is the governing equation of the seepage phenomena of homogeneous, isotropic earth dams, it has been confirmed that numerical analysis with high accuracy is possible by using the interpolation finite difference method (IFDM). In a previous paper, based on this numerical analysis method, the equivalent Kozeny (KZ) flow method was proposed as a new empirical method to calculate the seepage discharges and free surface locations of earth dams. Although this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…(57), there are two terms 𝑢 2𝑥2𝑦 and 𝑢 4𝑥4𝑦 that do not result in 𝑓 𝑘𝑥𝑙𝑥 . In the definition of 𝑜 𝑖𝑗 (12), an additional 𝑢 6𝑥6𝑦 term is generated.…”
Section: 𝐷 2⊗2 𝑢 2𝑥2𝑦mentioning
confidence: 99%
See 1 more Smart Citation
“…(57), there are two terms 𝑢 2𝑥2𝑦 and 𝑢 4𝑥4𝑦 that do not result in 𝑓 𝑘𝑥𝑙𝑥 . In the definition of 𝑜 𝑖𝑗 (12), an additional 𝑢 6𝑥6𝑦 term is generated.…”
Section: 𝐷 2⊗2 𝑢 2𝑥2𝑦mentioning
confidence: 99%
“…The author of the present study has also proposed and reported the interpolation FDM (IFDM) as a numerical calculation system with the above three characteristics. In this paper, which is based on published papers [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], I especially focus on the second of the above three features. In the area of computational fluid dynamics (CFD) using the finite difference method, many other valuable research results have been published in the treatment of irregular domains.…”
Section: Introductionmentioning
confidence: 99%